Preparation of Idebenone as a Thermosetting Nasal Gel for Better Bioavailability and Histopathological Effect - Kadhim, Hussein J.; Al-Kinani, Khalid K. (Journal of the Faculty of Medicine Baghdad, 2023)
Background Idebenone is an extensively metabolized drug with poor water solubility that is used to treat Leiber’s hereditary optical neuropathy. Objective This study aims to prepare idebenone nanoemulsion as a poloxamer-based nasal gel to overcome the extensive rate of hepatic metabolism for better bioavalability and lower histopathological effects on the nasal mucosa. Methods The formulation strategy was based on eliciting mutual concentration reduction between the nanoemulsion and the carrier gel by setting their gelation temperature between 30-32°C to overcome the mucociliary dose washout. The o/w nanoemulsions rely on cremophor EL and transcutol as an emulsifying system to stabilize idebenone-loaded lemongrass oil. The spontaneous emulsification method was used to prepare nanoemulsions that were characterized by zeta sizer while the thermosensitive hydrogels were prepared using the cold method. In-vitro dissolution test and ex-vivo permeation study through excised sheep nasal mucosa were performed to evaluate the enhanced permeation ratio, rate of permeation, and permeation coefficient. The histopathological effect of direct application on sheep nasal mucosa was studied using optical microscopy to evaluate cellular toxicity. Results The formula prepared from NE1 with poloxamer 407: poloxamer188 in concentrations 10:3% w/w respectively, showed almost complete drug release in 120 minutes due to complete polymers blend erosion. Furthermore, thermosensitive nano-emulgel at a temperature of gelation 31.8°C was obtained at much lower concentrations of poloxamer 407 (10%) compared to previous studies. Nanoemulsions retained their globular size below 100nm due to further gel entrapment stabilization. Conclusions Drug permeation through excised sheep nasal mucosa elicited an increase in enhanced permeation ratio to 20.3 times and other flux kinetics parameters compared to those of IDB oil dispersion. Direct cellular toxicity showed a minor inflammatory response characterized by serous infiltration of inflammatory cells and edema. In contrast, most of the epithelial cells retained their histological characteristics compared to control slides